Solution-Focused Brief Therapy (SFBT) Based Guidance for Student Academic Hardiness - Fajriani Fajriani; Abu Bakar; Fitra Marsela (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2021)
The background of the research is the importance of increasing competence for the younger generation as the nation's successor. This competence is related to the ability to face challenges, carry out commitments, and proper control in the midst of globalization which has positive and negative impacts. This capacity development can be developed through guidance interventions based on Solution-Focused Brief Therapy (SFBT). The purpose of this study was to analyzed the description of academic hardiness possessed by high school students in Aceh, and measured the effectiveness of guidance based on Solution-Focused Brief Therapy (SFBT) in developing academic hardiness of high school students in Aceh. This study used a quantitative approach with a quasi-experimental method (non-equivalent control group design). Data were collected using the modified Academic Hardiness Scale (AHS) from Benishek & Lopez based on three aspects of academic hardiness, specifically commitment, challenge, and control. The population of this research is 154 the MAS Imam Syafii students. The research sample consisted of 60 students who were divided into experimental and control groups. Based on the results of the paired samplet-test, there is a significant difference between the pre and post test results of students after being given SFBT-based guidance, but the results of the N-Gain analysis show that SFBT has a low effect in increasing the academic hardiness of MAS Imam Syafii students. To get a significant increase in academic hardiness, SFBT can also be given individually/group.